161k views
1 vote
Evaluate the step function for the given input values. g(x) = g(2) = g(–2) = g(5) =

User Ollyc
by
5.4k points

2 Answers

2 votes

Answer:

Explanation:

g(2) = g(–2) = g(5) is never true for the step function. One " = " symbol per pair of g values, please.

The step function, which you're calling "g(x)," is 0 from -infinity up to but not including 0. It's 1 from x just greater than 0 through infinity.

Thus:

g(2) = 1 because x is greater than 0.

g(-2) = 0 because x is less than 0.

g(5) = 1 because x is greater than 0.

User Eric Bonnot
by
6.0k points
7 votes

Answer:

g(2)= 3

g(-2)= -4

g(5)= 5

User Zauberfisch
by
5.8k points